Mortality Rate Prediction in ICU Using Logistic Regression Method - Sruthi, KV; Manju, K; Rashmi, R K; Krishnamouli, R (International Journal of Computer Sciences and Engineering, 2025)
High risk of illness is observed for the patients admitted in hospital’s cardiac intensive care units (ICU). Patient’s dead/alive categorical outcome prediction would benefits for patients as well as medical professionals in creating awareness and making clinical decisions respectively. In this work, a model is proposed for predicting life outcomes of cardiac patients admitted in ICU. The model is prepared on the basis of data collected from the regular medication treatments and clinical laboratory test results. A logistic regression model is prepared and compared with two standard algorithms in machine learning such as artificial neural network (ANN) and random forest algorithms, which are the classifiers of decision tree. The performance parameters were compared for both Synthetic Minority Oversampling Technique and stratified sampling for all predictive learning models. It is concluded that logistic regression with stratified sampling techniques would be preferable as a predictive model for the inconsistent time series data set.